LUKISAN SEBAGAI KOMODITAS INVESTASI BISNIS POTENSIAL - Namuri Migotuwio (Harmoni: Jurnal Pemikiran Pendidikan, Penelitian Ilmu-ilmu Seni, Budaya dan Pengajarannya, 2022)
Economic developments in various countries in the world, including Indonesia, have encouraged the arts sector as a field capable of producing tertiary commodities with great potential for optimization. Painting works of art in particular are present and able to become a basic need for the wealthy who are prestigiously involved in collector activities with high-value painting collection commodities. With professional management in the form of artistic activity organizing units developed by balancing supporting infrastructure, the sustainability of the painting business in the fine arts industry becomes a very interesting activity to be taken seriously.The resulting profitability is able to make painting commodities the only product with high margins. Although to achieve this requires a process that is not easy. An art businessman must be able to carefully read the market, integrate artists, curators, works of art, galleries, art events, collectors, and the media as a networking unit capable of building the reputation of works of art into high-value commodities.The mechanism of the painting business is certainly different from dealing with merchandise, because of the unique characteristics where price fluctuations can occur easily, and the artist's reputation is one of the factors determining price. How the role of a brand in a marketing context works, the risks that can occur and how a painting businessman carries out his function is an interesting analysis to study.